2004
DOI: 10.1007/bf03173238
|View full text |Cite
|
Sign up to set email alerts
|

Kindergarten cognitive intervention for reading difficulties: The PREP remediation in Greek

Abstract: This study reports two different experiments, as a part of a longitudinal study, that evaluated a cognitive intervention (PREP: PASS Reading Enhancement Program) to enhance early phonological processing skills, such as odd-word-out, segmenting, and blending, to kindergarten children at-risk for reading difficulties, in order to support the development of subsequent word reading skills. As part of the first experiment, thirty children aged 5.1, matched on the basis of age, gender, parental education levels, Non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 51 publications
1
32
0
5
Order By: Relevance
“…The corresponding probability level for simultaneous processing was .50. Finally, intervention studies that trained children on successive and simultaneous processing have shown significant effects on reading for both at-risk (e.g., Papadopoulos, Charalambous, Kanari, & Loizou, 2004;Parrila, Das, Kendrick, Papadopoulos, & Kirby, 2000) and reading-disabled children (e.g., Das, Mishra, & Pool, 1995;Hayward, Das, & Janzen, 2007) that were accompanied by an improvement in successive and simultaneous processing (e.g., Mahapatra, Das, Stack-Cutler, & Parrila, 2010).…”
Section: Pass Processes and Readingmentioning
confidence: 97%
“…The corresponding probability level for simultaneous processing was .50. Finally, intervention studies that trained children on successive and simultaneous processing have shown significant effects on reading for both at-risk (e.g., Papadopoulos, Charalambous, Kanari, & Loizou, 2004;Parrila, Das, Kendrick, Papadopoulos, & Kirby, 2000) and reading-disabled children (e.g., Das, Mishra, & Pool, 1995;Hayward, Das, & Janzen, 2007) that were accompanied by an improvement in successive and simultaneous processing (e.g., Mahapatra, Das, Stack-Cutler, & Parrila, 2010).…”
Section: Pass Processes and Readingmentioning
confidence: 97%
“…It is the number of accessed stimuli that may impact the RAN-reading relationship, such that higher correlations may be observed between RAN and reading when the RAN task requires the child to access 25 letters repeated twice (Clarke, Hulme, & Snowling, 2005) than when accessing 5 letters repeated ten times (Wolf et al, 1986). studies with Greek-speaking children showing satisfactory psychometric properties (e.g., Georgiou, Parrila, & Papadopoulos, 2008;Papadopoulos, Charalambous, Kanari, & Loizou, 2004). Testing was discontinued after six consecutive errors.…”
Section: Nonword Decodingmentioning
confidence: 99%
“…Los dos grupos, de intervención y comparación, se igualaron produciéndose variaciones significativas en las puntuaciones medias de ambos grupos desde el pretest al posttest. Se confirman así, los efectos positivos del programa PREP-L en procesamiento sucesivo y comprensión lectora en consonancia con otros estudios realizados (Papadopoulos, Charalambous, Kanari y Loizou, 2004;Papadopoulos, Das, Parrila y Kirby, 2003). Cuando los estudiantes mejoran la capacidad de decodificar aumentan su comprensión lectora, haciendo del PREP-L un programa preventivo, en el contexto RTI, porque permite: (a) evaluar tempranamente a los estudiantes, (b) implementar con ellos/as programas ajustados a sus necesidades de aprendizaje, (c) aplicarlos de manera intensiva, (d) supervisar el progreso de cada alumno/a durante la intervención y (e) ir tomando decisiones educativas en función de la evolución de sus aprendizajes (Jiménez et al, 2011).…”
Section: Discusión Y Conclusiónunclassified